Breathlessness and portable oxygen in chronic obstructive airways disease. Issue 4 (April 1983) - Waterhouse, J C; Howard, P
Abstract : Breathlessness was measured in 20 patients with severe chronic obstructive lung disease by the use of a visual-analogue scale. Severe resting arterial hypoxaemia was not a feature. The severity of breathlessness measured in this way did not correlate well with the results of spirometric tests or with walking ability. The use of portable oxygen was studied during simple walking tests for its effect on walking ability and the sensation of breathlessness. Portable oxygen improved exercise capacity but a placebo effect of the system probably accounted for some of the improvement. A clear improvement of distressing breathlessness was observed and represented a useful therapeutic response. Breathlessness and simple exercise ability were shown to respond independently to oxygen breathing. The value of short-term intermittent oxygen in patients with severe chronic obstructive lung disease needs to be evaluated in terms of both exercise ability and breathlessness.